ANALISIS FAKTOR-FAKTOR DALAM MENINGKATKAN DAYA SAING INDUSTRI KECIL MENENGAH DI TANGERANG SELATAN (STUDI KASUS : IKM SEPATU) - Edy Supriyadi; Endang Etty Merawaty; Derriawan Derriawan; Fachrudin Salim (Universitas Gadjah Mada, 2017)
The purpose of reserarch to determine the impact of condition factors, demand conditions, corporate strategy and competition, related industries and supporters, the role of government, the opportunity factor for competitiveness and productivity of Small Industry’s Shoes and also to know the development strategy of Small Industry’s Shoes in Tangerang District. The population in this research is the small Industry of the Textile, Leather, Footwear, and Multifarious Industry Sector at the Footwear Industry of the Sub-Sector in small industry’s Shoes located in Cikupa Tangerang Regency. The, total includes of 54 small industry’s Shoes consisting of 12 Sport Shoes Industry and 42 Shoes Industry Daily needs. In this case, the respondents are all the owner small industry’s shoe. Endogenous Variables are Competitiveness, while exogenous variables include, Condition Factor, Demand Condition, Industrial Strategy and Competitor, Related and Supporting Industries, The results this research found that there are any significant difference among Condition Factors, Demand Factors, Supporting and Related Industries, Opportunity Factors, Industry Strategy and Competition, Opportunity Factors and Government role toward Competitiveness